2015
DOI: 10.1590/1678-4499.267
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de cultivares de citros enxertadas sobre o trifoliateiro 'Flying Dragon' e limoeiro 'Cravo' em fase de formação do pomar

Abstract: The experimental design was a randomized block, in a 2 × 5 factorial, being evaluated the 2 mentioned rootstocks and 5 canopies cultivars.The evaluated canopies cultivars were the acid lime 'Tahiti' and the sweet oranges 'Natal', 'Bahia', 'Lima Sorocaba' and 'Pera'. Biometric evaluations were made to estimate the vegetative vigor index (VVI), the canopy volume and coverage rates in the lines and rows of cultivation, reached 36 months after planting. Under the conditions of this experiment, it was found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 13 publications
1
9
0
2
Order By: Relevance
“…these results corroborate Portella et al (2016), who observed that 'limeira' trifoliate reduced height, vegetative vigor index, coverage rates in the row and inter-rows, and canopy volume of 'tahiti' acid lime in irrigated cultivation under the climatic conditions of northern Rio de Janeiro. lima, et al (2014) also observed in northern Rio de Janeiro that the size of 'Lima' orange tree was reduced by 56% when grafted on 'limeira' trifoliate, having 'Rangpur' lime as reference in irrigated cultivation.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…these results corroborate Portella et al (2016), who observed that 'limeira' trifoliate reduced height, vegetative vigor index, coverage rates in the row and inter-rows, and canopy volume of 'tahiti' acid lime in irrigated cultivation under the climatic conditions of northern Rio de Janeiro. lima, et al (2014) also observed in northern Rio de Janeiro that the size of 'Lima' orange tree was reduced by 56% when grafted on 'limeira' trifoliate, having 'Rangpur' lime as reference in irrigated cultivation.…”
Section: Resultssupporting
confidence: 90%
“…although 'Rangpur' lime is considered a rootstock suitable for 'tahiti', it is susceptible to gummosis caused by Phytophthora citrophthora and Phytophthora parasitica, which reduces plant longevity (CaRvalhO et al, 2016). In addition, plants grafted on 'Rangpur' lime tree reach excessive sizes in the climate of northern minas Gerais, which requires the use of wide spacing or pruning.…”
Section: Introductionmentioning
confidence: 99%
“…Sand, silt, and clay concentrations, textural class, density (SD), hydraulic conductivity (K 0 ), and soil mechanical resistance to penetration (SMRP) throughout the profile of an Oxisol. Lagoa do Coco Farm, BA, Brazil canopy volume (MCV; m 3 ), according to Portella et al (2016), using Eqs. 1 to 4: Soil moisture was monitored by time domain reflectometry (TDR), with sensors distributed vertically (0-0.20, 0.20-0.40, 0.40-0.70, 0.70-1.10, and 1.10-1.70 m), at 0.5 m of the plant stem, perpendicularly to the planting row, at every 0.20 m of the soil surface.…”
Section: Methodsmentioning
confidence: 99%
“…These data were used to calculate, according to Portella et al (2016), the canopy cover rate in the row (CCR-R), canopy cover rate in the interrow (CCR-I), vegetative vigor index (VVI) and mean canopy volume (CV), according to the equations:…”
Section: Biometric Evaluations Of Plant Shootsmentioning
confidence: 99%